2014
DOI: 10.1210/jc.2014-1575
|View full text |Cite
|
Sign up to set email alerts
|

Both Low and High Serum IGF-1 Levels Associate With Increased Risk of Cardiovascular Events in Elderly Men

Abstract: Both low and high serum IGF-1 levels are risk markers for CVD events in elderly men. The association between high serum IGF-1 and CVD events is mainly driven by CHD events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
1
37
0
1
Order By: Relevance
“…IGF-I is involved in a variety of physiological and pathological processes, such as the regulation of blood pressure and body composition, insulin sensitivity and peripheral vascular resistance. The complexity of the IGF-I mechanism is illustrated by the results of a large Swedish cohort study, which shows that both low and high IGF-I levels associate with increased risk of cardiovascular events in elderly men (Carlzon et al 2014). In conclusion, DHEAS and IGF-I may contribute to the link between early growth and adult diseases, but the mechanism is not fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I is involved in a variety of physiological and pathological processes, such as the regulation of blood pressure and body composition, insulin sensitivity and peripheral vascular resistance. The complexity of the IGF-I mechanism is illustrated by the results of a large Swedish cohort study, which shows that both low and high IGF-I levels associate with increased risk of cardiovascular events in elderly men (Carlzon et al 2014). In conclusion, DHEAS and IGF-I may contribute to the link between early growth and adult diseases, but the mechanism is not fully understood yet.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies have shown that lower serum IGF-1 is associated with an increased risk of ischemic heart disease, as well as increased incidence of coronary calcification and carotid atherosclerotic plaques (45)(46)(47)(48)(49)(50). There have also been meta-analyses and other studies including a recent prospective study in elderly men that show a U-shaped association between serum IGF-1 levels and cardiovascular events or all-cause mortality (51,52). These varying results likely reflect the complexity of IGF-1 effects on the vasculature that are dependent on a multitude of factors, including the predominant cell type within the atheroma to which IGF-1 targets or the degree of disease progression when IGF-1 effects were examined.…”
Section: Ldlrmentioning
confidence: 99%
“…In obese adults, IGF-I levels are inversely related to cardiometabolic risk [1, 2] and low IGF-I levels are associated with increased risk of isch emic heart disease [3]. In the elderly, both low and high IGF-I levels have been associated with cardiovascular disease [4]. …”
Section: Introductionmentioning
confidence: 99%